(untitled) (Cadernos de Sociomuseologia, 2022)
While discussing the decolonization of museums and the decoloniality of museology, this investigation questions the experiences of black women in AfroBrazilian community museums, seeking to reflect the dimension of race and the intersectionality of gender and race in Brazilian museology. The vast majority of Brazilian museum institutions were constituted from the logic of modernity / coloniality and, consecrated themselves presenting Eurocentric, colonizing, encyclopedic, hierarchical characteristics, preserving the material culture of the economic and political elite and under-representing indigenous and black cultures. In this process, black women in museums brought together the invisibility, the silencing and the erasing given to blacks and women of dehumanization, of representation in stereotyped and hypersexualized images frozen in the stigma of enslavement. Based on the assumptions of Decolonial Museology that brought the issue of race and racism to the foreground, the reduction of injustices and inequalities, reinforced community participation and recognized new practices for the preservation of memory. Afro-Brazilian community museums were analysed in search for the role of black women; epistemic disobedience, recognition of race as structural; the collective construction and the search for an end to inequalities. In short, the struggle for a new world order that has the museum as a tool to face racism, to promote racial equality and to empower and social development. Keywords: Sociomuseology; Decoloniality; Interseccionalit of race and gender; black women; Afro-Brazilian museums